Role of saline infusion sonography in evaluation of abnormal uterine bleeding - Gupta, Neerja; Singh, Geeta; Jain, Bharti; Garg, Satakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Abnormal uterine bleeding (AUB) is one of the most common reasons for women seeking gynaecological advice. The objective of this study was to determine the accuracy of Transvaginal sonography (TVS) and Saline Infusion Sonography (SIS) in evaluation of Abnormal Uterine Bleeding (AUB) and to compare the diagnostic accuracy after hysterectomy. Methods: Prospective, comparative study of TVS and SIS in evaluation of AUB in patients who are being subjected to hysterectomy with uterus of less than 12 weeks. Results: 100 patients were included in the study. 98% were of 30-50 years. Heavy menstrual bleeding was the commonest symptom (52%) and most common finding was fibroid, and Polyp followed by abnormal endometrium. The overall sensitivity and specificity when correlated with operative and HPE were 66% and 88% respectively for TVS and 82% and 95% for SIS respectively. The false positive and false negative rates were more in TVS compared to SIS. Commonest histopathology was intramural fibroid in 42% followed by sub mucus myoma in 21%, polyp 18% and endometrial hyperplasia 10%. Conclusions: SIS is a simple highly sensitive and specific technique to detect intra uterine pathology in the evaluation of AUB when TVS findings are inconclusive.